Cyclin E1/CDK2 activation defines a key vulnerability to WEE1 kinase inhibition in gynecological cancers - Daehwan Kim; Heekyung Chung; Wen Liu; Kangjin Jeong; Tugba Y. Ozmen; Furkan Ozmen; Matthew J. Rames; Sangyub Kim; Xiao Guo; Nathan Jameson; Petrus R. de Jong; Steven Yea; et al. (npj Precision Oncology)
Abstract Upregulation of Cyclin E1 and subsequent activation of CDK2 accelerates cell cycle progression from G1 to S phase and is a common oncogenic driver in gynecological malignancies. WEE1 kinase counteracts the effects of Cyclin E1/CDK2 activation by regulating multiple cell cycle checkpoints. Here we characterized the relationship between Cyclin E1/CDK2 activation and sensitivity to the selective WEE1 inhibitor azenosertib. We found that ovarian cancer cell lines with high levels of endogenous Cyclin E1 expression or forced overexpression were exquisitely sensitive to azenosertib and these results extended to in vivo models of ovarian and uterine serous carcinoma. Models with high Cyclin E1 expression showed higher baseline levels of replication stress and enhanced cellular responses to azenosertib treatment. We found azenosertib synergized with different classes of chemotherapy and described distinct underlying mechanisms. Finally, we provided early evidence from an ongoing phase I study demonstrating the clinical activity of monotherapy azenosertib in patients with Cyclin E1/CDK2-activated ovarian and uterine serous carcinomas.